2020
DOI: 10.3390/su12208328
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Efficiency of Composite Beam Application in Multi-Storey Buildings

Abstract: Over the past decade, several types of composite slim floor constructions have been used in multi-storey buildings in Lithuania. In order to study the efficiency of composite beam application in steel-framed multi-storey buildings, Thorbeam (A1), Deltabeam (A2), slim floor beam (A3) and asymmetric slim floor beam (A4) were chosen and evaluated according to nine assessment criteria (beam cost (K1), initial preparation on site (K2), installation time (K3), complexity of installation technology (K4), labour costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The steel-concrete composite floor system is more advantageous than steel floor systems for reducing material quantities and GHGs related to embodied CO 2 emissions because it can increase the stiffness and strength of the section owing to the composite effect of steel and concrete [12]. Kinderis et al [13] reported that the composite floor system, the so-called Deltabeam, can reduce the building's height compared to concrete beams. Du et al [14] experimentally confirmed that high-strength materials can dramatically improve the flexural performance of the steel-concrete composite floor system.…”
Section: Introductionmentioning
confidence: 99%
“…The steel-concrete composite floor system is more advantageous than steel floor systems for reducing material quantities and GHGs related to embodied CO 2 emissions because it can increase the stiffness and strength of the section owing to the composite effect of steel and concrete [12]. Kinderis et al [13] reported that the composite floor system, the so-called Deltabeam, can reduce the building's height compared to concrete beams. Du et al [14] experimentally confirmed that high-strength materials can dramatically improve the flexural performance of the steel-concrete composite floor system.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on these steel composite beam systems have verified the structural performance of the connection or unit system through experiments [13][14][15][16][17]. Kinderis et al [18] showed the efficiency of steel composite beam systems in terms of cost; however, previous studies on steel composite beam systems lack the analysis of the environmental impact assessment.…”
Section: Introductionmentioning
confidence: 99%